METHEYLENE BLUE ADSORPTION AND PREPARATION SILVER BOUND TO ACTİVATED CARBON WITH SOL-GEL METHOD - Ömer Faruk Soydan; Esra Altıntığ (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Thisstudy examines the characterization and adsorption features of silver that wasadded to oxygen containing activated carbons using the sol-gel method. Thesurface area of the silver coated activated carbon (AC/Ag) Nano-composites,which were prepared using the sol-gel method, was measured with theBraunauer-Emmett-Teller surface area calculation method according to N2adsorption at 77 K. The microstructure and surface morphologies of the AC/AgNano-composite samples were examined with the use of Scanning ElectronMicroscope. Methylene Blue removal was performed with AC/Ag-1 with 658.488 m2/g,which had the highest surface area, and the Qmax value was calculated as 416.66 mg/g.